2014
DOI: 10.1364/ol.39.000888
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of high-stability 10 GHz local oscillator over 100 km optical fiber with accurate phase-correction system

Abstract: We have developed a radio-frequency local oscillator remote distribution system, which transfers a phase-stabilized 10.03 GHz signal over 100 km optical fiber. The phase noise of the remote signal caused by temperature and mechanical stress variations on the fiber is compensated by a high-precision phase-correction system, which is achieved using a single sideband modulator to transfer the phase correction from intermediate frequency to radio frequency, thus enabling accurate phase control of the 10 GHz signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Synchronization is vital for very large baseline interferometry application. Successful stable time and frequency signals sent over optical¯bers (Calhoun et al, 2007) of 4.6 km (Mullavey et al, 2010, 20 km (Baldwin et al, 2012) and 100 km (Wang et al, 2014) have been reported.…”
Section: Introductionmentioning
confidence: 98%
“…Synchronization is vital for very large baseline interferometry application. Successful stable time and frequency signals sent over optical¯bers (Calhoun et al, 2007) of 4.6 km (Mullavey et al, 2010, 20 km (Baldwin et al, 2012) and 100 km (Wang et al, 2014) have been reported.…”
Section: Introductionmentioning
confidence: 98%
“…The distribution of ultra-stable radio frequency (RF) standard plays an important role in numerous areas, such as global navigation system, fundamental physics, astrophysics [1][2][3]. Newly developed RF dissemination schemes have attracted widespread research interest [4][5][6][7][8][9][10][11]. By modulating an RF reference onto telecommunications-grade wide-linewidth lasers (typical linewidth > 100 kHz), fiber-based RF transfer has been recognized as an ideal solution for ultra-long-haul dissemination due to the advantages of low attenuation, wide bandwidth and immunity to electromagnetic interference [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Based either on the global positioning system or two-way satellite time and frequency transfer [2][3][4], the traditional satellite links have met bottlenecks to further improve their performance to meet the demand of many particular applications, such as the comparison of atomic clocks, tests of the fundamental constants' stability, geodesy, cosmology, and so on [5][6][7][8]. Optical fiber links are considered to be a promising alternative because of their dependability and better performance, as has been proved by several groups in recent years [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Although ultrastable optical carrier transfer has shown superior stability around 10 −19 , its application is limited to the comparison between optical clocks in laboratories because it is very expensive for an ordinary user to perform frequency downconversion.…”
mentioning
confidence: 99%
“…Therefore, the dissemination of radio frequency (RF) is still widely studied today [14][15][16][17][18][19][20][21][22]. Most of the methods used in these works are generally based on the measurement of round-trip phase fluctuation and active compensation of the outgoing signal phase in the electric domain [15][16][17][18][19][20][21] or the optical domain [14,15,22]. However, the actively compensating systems, by voltage-controlled oscillators or a piezoelectrical transducer, are complex because the phase stabilization is based on a feedback loop, and therefore active controlling, such as the proportional-integral-derivative algorithm, is indispensable.…”
mentioning
confidence: 99%